1986
DOI: 10.1007/bf00965942
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual heterogeneity of molecular weight of human brain neutral sphingomyelinase determined by radiation inactivation method

Abstract: The molecular weight (Mr) of the membrane-bound neutral sphingomyelinase from human brain was determined using the radiation inactivation procedure. Previous studies on three human brains suggested a Mr of 165 +/- 25 kDa (J. Neurochem. 1985, 45:630-632). We now report that in another human brain the neutral sphingomyelinase had a Mr of 740 +/- 100 kDa; this higher Mr was not accompanied by differences in enzymatic properties nor heat-stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…2 Several different forms of mammalian SMases have been identified, including: (a) a lysosomal SMase that is present in all tissues, acts optimally at low pH, and shows no dependence on divalent cations (11). This enzyme, which is defective in types A and B Niemann-Pick disease (11), has been purified and cloned (12), and mice in which the gene encoding lysosomal SMase has been inactivated have recently been generated (13,14); (b) a neutral, membrane-associated, Mg 2ϩ -stimulated SMase that is found predominantly in brain and kidney (15) and that is known to arise from a separate gene from lysosomal SMase (16); (c) a cytosolic SMase that like Mg 2ϩ -stimulated SMase has a neutral pH optimum but no dependence of divalent cations (17); and (d) an acidic, Zn 2ϩ -stimulated SMase (Zn-SMase) so far reported only in fetal bovine serum and to a lesser degree in newborn human serum (18).…”
Section: Mammalian Smasesmentioning
confidence: 99%
“…2 Several different forms of mammalian SMases have been identified, including: (a) a lysosomal SMase that is present in all tissues, acts optimally at low pH, and shows no dependence on divalent cations (11). This enzyme, which is defective in types A and B Niemann-Pick disease (11), has been purified and cloned (12), and mice in which the gene encoding lysosomal SMase has been inactivated have recently been generated (13,14); (b) a neutral, membrane-associated, Mg 2ϩ -stimulated SMase that is found predominantly in brain and kidney (15) and that is known to arise from a separate gene from lysosomal SMase (16); (c) a cytosolic SMase that like Mg 2ϩ -stimulated SMase has a neutral pH optimum but no dependence of divalent cations (17); and (d) an acidic, Zn 2ϩ -stimulated SMase (Zn-SMase) so far reported only in fetal bovine serum and to a lesser degree in newborn human serum (18).…”
Section: Mammalian Smasesmentioning
confidence: 99%
“…Nevertheless, S-SMase requires exogenously added Zn 2ϩ for activation in in vitro assays, whereas L-SMase isolated from cell or tissue homogenates does not (16). In fact, the lack of stimulation of L-SMase by any cations and its lack of inhibition by EDTA has led to a long-standing body of literature labeling L-SMase as a "cation-independent" enzyme (1).…”
Section: Smasesmentioning
confidence: 99%
“…1 (SM phosphodiesterase, EC 3.1.4.12) have been implicated in a wide variety of physiologic and pathophysiologic processes, including lysosomal hydrolysis of endocytosed SM (1,2), ceramide-mediated cell signaling (3,4), membrane vesiculation (5,6), alterations in intracellular cholesterol trafficking (5,(7)(8)(9), and atherogenesis (10 -13). One type of mammalian SMase is a magnesium-dependent, membrane-bound neutral SMase, and Tomiuk et al (14) have recently reported the cloning of an enzyme that has several properties in common with this SMase.…”
Section: Smasesmentioning
confidence: 99%
“…At least seven different SMases have been identified (14). Acid lysosomal SMase is found ubiquitously in tissues and defective in types A and B Niemann-Pick disease (15). A variety of cell types present in atherosclerotic lesions secrete SMase (16).…”
mentioning
confidence: 99%